Revised intra-generic grouping of Bursaphelenchus Fuchs, 1937 (Nematoda: Aphelenchoididae) (Journal of Nematode Morphology and Systematics, 2012)
Based on a complex of characters, in particular the number of incisures in the lateral field, arrangement ofmale caudal papillae, presence or absence of vulval flap, spicule shape, position of excretory pore and length of postvulval uterus branch, the taxonomic grouping of Bursaphelenchus is revised. The genus is divided into seven groups with four incisures in the lateral field (xylophilus, okinawaensis, africanus, fungivorus, cocophilus, kevini and sexdentati groups), four groups with three incisures (eggersi, eremus, hofmanni and leoni groups) and two groups with two incisures (abietinus and sinensis groups). This system is supported by phylogenetic trees based on rDNA partial sequences (SSU, ITS1/2, LSU D2/D3). Several species could not be grouped and require further investigation. The four-incisure groups cluster together in a big clade in molecular trees, with the exception of the scolytid-vectored sexdentati group, which shares a big clade with the species having reduced number of incisures. Bursaphelenchus abruptus usually clusters outside the genus in molecular trees, as also do Devibursaphelenchus lini (syn. B. lini) and D. hunanensis (syn. B. hunanensis). Bursaphelenchus digitulus Loof, 1964 is newly combined to Parasitaphelenchus digitulus Loof, 1964. The groups are morphologically characterized, and a dichotomous key for their identification is given.